The influence of leadership style, training and development through employee engagement on senior manager productivity: a case study at Bank Lampung / Mira Rozanna and Ahmad Adriansyah - Rozanna, Mira (UiTM Cawangan Johor, 2023)
Human resource management is one of the essential aspects to improve the company 's performance in achieving the vision and mission of the organization. To face business competition for banks, they need to be supported by a productive leadership and resource role. Based on this, the author is interested in investigating employee productivity factors that affect banks ' performance. Moreover, concerning the field's research results, several findings have made the author focus on studying leadership style, training and development, and employee engagement on employee productivity. A sample of the respondents consisted of 57 Senior Manager Officers of Bank Lampung employed in this research. The analysis technique used was structured equation modeling (SEM) with the Partial Least Square (PLS research tool and the data retrieval method using questionnaires to all the respondents. The research analysis revealed leadership style, training and development through employee engagement significantly affected employee productivity. Keywords: Leadership Style, Training and Development, Employee Engagement, Employee Productivity